Molecular Detection of Pap II, OmpA, and LuxR Genes Responsible for Biofilm Formation in Acinetobacter baumannii Isolated from Hospitalized Patients - Estabraq Ali Maklef; Amal A. Kareem; Susan F. K. Al-Sudani (Medical Journal of Babylon)
Background: The first pathogen to be designated a “red-alert” human pathogen is Acinetobacter baumannii, which is on the list of infections that must be treated urgently with new antibiotics. Infections due to this bacterium are on the rise, especially in patients admitted to hospital intensive care units. It can create biofilms on both biotic and abiotic surfaces. Objectives: This study aimed to detect biofilm formation by A. baumannii phenotypically and genotypically. Materials and Methods: A total of 250 samples were subjected to bacterial identification using the VITEK-2 compact system, which showed 42 A. baumannii isolates. Biofilm formation was phenotypically investigated using the microtiter plate method. Results: The results revealed three stages of biofilm formation: 5 (11.6%) nonbiofilm, 13 (30.2%) weak biofilm, 15 (34.9%) moderate, and 10 (23.3%) strong biofilm formation. The isolates from intensive care unit (ICU) patients had strong, moderate, weak, and nonforming biofilm ability in higher rates of biofilm producers compared with the isolates from samples of hospital wards. The polymerase chain reaction (PCR) products showed genotypically positive results as follows: PapII 12 (31.5%), OmpA 11 (28.9%), and LuxR 8 (21%) out of 38 positive samples of A. baumannii for all genes. Conclusion: Isolates of A. baumannii appeared in different stages of biofilm formation with a higher percentage rate in the ICU compared with hospitalized patients. The PCR products for isolates of A. baumannii showed that PapII, OmpA, and LuxR showed positive results.